High contrast cartilaginous endplate imaging using a 3D adiabatic inversion‐recovery‐prepared fat‐saturated ultrashort echo time (3D IR‐FS‐UTE) sequence. (5th July 2021) - Lombardi, Alecio F.; Wei, Zhao; Wong, Jonathan; Carl, Michael; Lee, Roland R.; Wallace, Mark; Masuda, Koichi; Chang, Eric Y.; Du, Jiang; Ma, Ya‐Jun
Abstract : Ultrashort echo time (UTE) sequences can image tissues with transverse T  2 / T  2 * relaxations too short to be efficiently observed on routine clinical MRI sequences, such as the vertebral body cartilaginous endplate (CEP). Here, we describe a 3D adiabatic inversion‐recovery‐prepared fat‐saturated ultrashort echo time (3D IR‐FS‐UTE) sequence to highlight the CEP of vertebral bodies in comparison to the intervertebral disc (IVD) and bone marrow fat (BF) at 3 T. The IR‐FS‐UTE sequence used a 3D UTE sequence combined with an adiabatic IR preparation pulse centered in the middle of the water and fat peaks, while a fat saturation module was used to suppress the signal from fat. A slab‐selective half pulse was used for signal excitation, and a 3D center‐out cones trajectory was used for more efficient data sampling. The 3D IR‐FS‐UTE sequence was applied to an ex vivo human spine sample, as well as the spines of six healthy volunteers and of three patients with back pain. Bright continuous lines representing signal from CEP were found in healthy IVDs. The measured contrast‐to‐noise ratio was 18.5 ± 4.9 between the CEP and BF, and 20.3 ± 4.15 between the CEP and IVD for the six volunteers. Abnormal IVDs showed CEP discontinuity or irregularity in the sample and patient studies. In conclusion, the proposed 3D IR‐FS‐UTE sequence is feasible for imaging the vertebral body's CEP in vivo with high contrast. Abstract : A 3D IR‐FS‐UTE sequence combining a 3D UTE sequence with an adiabatic pulse centered on water and fat spectrum frequencies was implemented and applied to two ex vivo samples and the spines of three healthy volunteers and three patients with back pain. The proposed 3D IR‐FS‐UTE sequence showed high contrast‐to‐noise ratio between the CEP, the BF, and the IVD.